Exports “brother-boost”: the trade-creation and skill-upgrading effect of Venezuelan forced migration on Colombian manufacturing firms - Lombardo, Carlo (2021)
This paper studies the impact of a massive skilled labor supply shock on Colombian manufacturing firms’ exports, the Venezuelan exodus. We exploit crosssectional and time variability of Venezuelan forced migrants’ settlements in Colombian sub-national areas through an enclave instrumental variables approach to account for the selection of immigrants’ location. Using yearly customs data from 2013 to 2019, we find that the Venezuelan migration improved Colombian manufacturing firms’ export performance, particularly to high-income countries of the OECD located in North America and low-income countries. This effect was stronger for firms that exported less prior to the exodus (2012). Furthermore, using a detailed yearly panel of manufacturing firms from 2013 to 2019 we identify the potential labor market driving mechanism of the trade-creation effect: immigrants lowered exporting firms’ blue-collar wages, and allowed them to upgrade their labor force skill composition, namely firms were able to hire workers more compatible with exports to developed destinations.